Analysis of Marketing Strategy in Increasing Sales Volume: A Case Study of Sushi Geprek Bidadari - Tria Handayaningrum; Wulan Budi Astuti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The development of science and technology affects all areas of life, including the business sector. The purpose of this research is to find out the marketing strategy in increasing sales volume at Sushi Geprek Bidadari. This research method is descriptive qualitative. The results of this study show that the strategy undertaken to increase sales volume of Sushi Geprek Bidadari is by first paying attention to what products will be sold by paying attention to who the market segment is, by paying attention to the level of products sold in the form of sushi with variations of geprek chicken, geprek eggs, geprek indomie with variant levels 1-0 whose market segments are children, youth and adults and product classification by always arranging merchandise neatly, to make it easier for owners to serve consumers. Second, setting the right price and not too expensive and considering product quality, which will affect profits and business sustainability. The price set in the bidadari susi geprek business is in the general price range, while the profit sometimes increases, sometimes decreases or is unstable. Meanwhile, to maintain his business, the owner of Sushi Geprek Bidadari makes variations of Nisi Sushi that are different from sushi in general. Third, distributions include consumer information obtained from the social media of Sushi Geprek Bidadari and prices for sushi products written on the menu. Fourth, promotions include sales promotions by promoting via WhatsApp, Instagram and GoJek. The strategy used by the owner of Sushi Geprek Bidadari is quite good.